Stochastic Semigroups and Random Mass Transfer - Feshchenko, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider the problem of random mass transfer on a metric compactum defined by a purely discontinuous stochastic semigroup \(T_t^s\) . We give a description of this semigroup based on a Markov process with random transition probability. We present conditions for the independence of measure-valued processes of the form \(T_t^0 μ_{0}\) , depending on the initial mass μ0.